Future-proofing imperatives for remote online teaching, learning and student support in the context of pandemic change and beyond: A case for South African higher education transformation - van Staden, D.; Naidoo, P. (South African Journal of Higher Education, 2021)
South Africa’s Plan for Higher Education identified equity and redress as key objectives guiding institutional transformation. This encompasses granting individuals fair opportunities to enter higher education and succeed therein. The COVID-19 pandemic which abruptly disrupted the 2020 academic year highlighted several challenges which have implications for student success. Academic continuity in the form of online learning was pursued by most higher education institutions. However, the remoteness of rural communities, which typifies the home environments for many South African students, threatened to exclude such students from online learning activities. The lack of access to digital devices as well as reliable internet connectivity in many of these communities impacted students’ ability to engage in online learning as well as access campus-based support services. The imposed lockdown therefore caused heightened anxiety and feelings of isolation from academic activities amongst the South African student population. Since access to on-campus support systems was no longer possible, student wellness and ongoing academic engagement was potentially compromised. Increasingly, the mental health cost of remote learning was becoming apparent, with higher education institutions compelled to rethink how student support services are delivered. In the absence of face-to-face support services during the hard lock-down period, the emergent need was to identify new ways of reaching out to displaced students who may be experiencing both academic and personal distress under conditions of daunting technological changes and virtual forms of engagement, social isolation, socio-economic disadvantage and psycho-social stressors. While blended learning and hybrid forms of holistic student support were accelerated by the advent of the Covid-19 pandemic, the blended approach has become an indelible reality of Higher Education that is here to stay. As such, reflections on how student support services at universities in South Africa have adapted and need to continuously evolve in the face of an uncertain world, is both timely and necessary if the goal of promoting equal access and success in Higher Education – for all - is to be fully realized.